The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1145/3427333
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking the Dual Gaussian Distribution Model for Predicting Touch Accuracy in On-screen-start Pointing Tasks

Abstract: The dual Gaussian distribution hypothesis has been used to predict the success rate of target pointing on touchscreens. Bi and Zhai evaluated their success-rate prediction model in off-screen-start pointing tasks. However, we found that their prediction model could also be used for on-screen-start pointing tasks. We discuss the reasons why and empirically validate our hypothesis in a series of four experiments with various target sizes and distances. The prediction accuracy of Bi and Zhai's model was high in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 54 publications
0
4
1
Order By: Relevance
“…We found that 2,666 data points passed the bivariate normality test (80.1%). These rates were lower than those in previous studies [7,45].…”
Section: Model Fittingcontrasting
confidence: 81%
See 4 more Smart Citations
“…We found that 2,666 data points passed the bivariate normality test (80.1%). These rates were lower than those in previous studies [7,45].…”
Section: Model Fittingcontrasting
confidence: 81%
“…The findings and model validation in this study were limited to the extent of our experimental design, such as the target sizes we used. While we assumed that the target distance does not affect the endpoint variability in accordance with previous studies [6,21,45], this assumption does not hold when users exhibit ballistic movements [5,18]. Our instruction to select a target as rapidly and accurately as possible is just one strategy from among various speed-accuracy arXiv, 2023, balances.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations